Sexualidade: diálogos entre pais e filhos(as) Uma leitura hermenêutica a partir da Gestalt-terapia. - Lira, Vladya Tatyane Pereira de (2022)
The debate about sexuality has been a challenge in our society because it is still considered a very uncomfortable and taboo theme and it is the least discussed among the conversations. Although this society look at sexuality, some authors signify the importance of the dialogue between parents and young children, because they consider that it is inside the family that we can make up some space to open up our minds to the matter in a very loving and comprehensive way. Before that, we had as objective to understand from the Gestalt-Therapy in which way this discussion has been established in the family specially between parents and children. Other specific objectives are to study how the communicative approach happens about this matter. Moreover, to understand how the heterocisnormatividade influences communication about sexuality. It is proposed qualitative research in a phenomenological hermeneutical based on interviews with youngsters between 19 to 24 years old, from both genders (males and females) that went to private schools in the region of Recife and whereabouts and also to their parents. To data analyzes it was used the qualitative analysis procedures from the Gadamer Hermeneutical relating these theories to the understanding of the post- structuralist theory about sexuality. As a result, there has been a dialogue between parents and children, even though it doesn’t represent the Brazilian reality.